Synthetic organometallic radical chemistry in water - Postigo, Jose Alberto (2009)
Several organic radical transformations in aqueous media using organometallic chemistry are presented. Group XIV-elements, such as Si and Ge, and Sn-centered radicals make use of novel methodologies in water which employ both hydrophilic and lipophilic substrates without the requirements of surfactants. Different radical initiation techniques that account for effective initiation of the radical chain reactions in aqueous media are also described, such as the thermal decomposition of azo compounds, the direct photolysis (in the absence of an organic peroxide or other photolytic radical promoter) of silanes, dioxygen initiation techniques, and radical initiation in the absence of solvent, and in the presence of adventitious oxygen. Hydrometallation of multiple bonds with (Me3Si)3SiH and germane analogs in water are also described with the above mentioned initiating techniques, under solvent-free conditions, and performed in continuous flow microreactors. The use of other metal-centered radicals that promote synthetically useful organic transformations in water, such as Mg, Mn, and Zn, is presented. These transformations encompass simple organohalide reductions, and several types of carbon-carbon bond forming reactions, demonstrating the wide scope of organometallic radical chemistry in water for accomplishing organic transformations. Group XIII- centered radicals are also shown to be excellent mediators for organic radical reactions in water, such as Barbier-type alkylations and allylations of carbonyl compounds.